1994
DOI: 10.1111/j.1365-2362.1994.tb02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum angiotensin converting enzyme activity in type T insulin—dependent diabetes mellitus: its relation to metabolic control and diabetic complications

Abstract: Serum angiotensin-converting enzyme (ACE) was measured in 150 insulin-dependent diabetes mellitus (IDDM) patients and 72 healthy subjects by radioassay, using [3H]-hippuryl-glycyl-glycine as a substrate. Mean (SD) serum ACE activity in diabetic patients was 120 +/- 33 nmol ml-1 min-1 (range 46-215) and was significantly increased by 56% compared to control values (77 +/- 23 nmol ml-1 min-1, range 46-125, P < 0.001). ACE activity > 125 nmol ml-1 min-1 was observed in 60 of 150 IDDM patients. 96 IDDM patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 9 publications
2
26
1
6
Order By: Relevance
“…Coppey et al (2006) have shown that treatment with either enalapril, an ACE inhibitor, or L-158809, an AT1 receptor antagonist, prevents or reverses diabetic neuropathy in STZ-induced diabetic rats (STZ rats). Although the evidence indicates that RAS activity is increased in diabetes (Van Dyk et al, 1994;van Dijk et al, 2001), the role of spinal RAS on diabetic neuropathic pain has not been reported to date. Thus, we hypothesized that it was important to examine whether spinal RAS is necessary and sufficient for diabetic neuropathic pain in the STZ mouse model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Coppey et al (2006) have shown that treatment with either enalapril, an ACE inhibitor, or L-158809, an AT1 receptor antagonist, prevents or reverses diabetic neuropathy in STZ-induced diabetic rats (STZ rats). Although the evidence indicates that RAS activity is increased in diabetes (Van Dyk et al, 1994;van Dijk et al, 2001), the role of spinal RAS on diabetic neuropathic pain has not been reported to date. Thus, we hypothesized that it was important to examine whether spinal RAS is necessary and sufficient for diabetic neuropathic pain in the STZ mouse model.…”
Section: Discussionmentioning
confidence: 98%
“…In the diabetic state, there is an increase in plasma ACE activity and levels of Ang II (Van Dyk et al, 1994;van Dijk et al, 2001) and there have been many studies conducted on the relationship between RAS and diabetic complications. One of the outcomes of RAS activation is the hypertrophy of various renal cells promoted by Ang II, which leads to the development of diabetic nephropathy (Leehey et al, 2000;Vidotti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have suggested that high serum levels of ACE were especially associated with PDR. 6 The biological mechanism through which ACE I/D polymorphism may be related to an increased risk of DR is unclear. Serum ACE concentrations are significantly higher in those carrying the D/D genotype than in those carrying the I/D or the I/I genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the relationship between the systemic RAS and endocrine pancreas function has largely been concerned with the role of Ang II in the the hypertension of diabetes, its complications such as nephropathy, and retinopathy, and their possible control by drugs regulating its action (Hsueh & Anderson 1993, Vandyk et al 1994, Tait & Tait 1997, Goa 1997, Allen 1997, Anderson 1997, Kim et al 1997, Chaturvedi et al 1998. In addition, studies with experimental animals as well as patients have shown that the systemic RAS may be perturbed in diabetes, though the situation is complex, and opposing effects, for example on Ang II receptor function have been reported in different tissues (Sechi et al 1994, Cheng et al 1994, Fliser et al 1997, Brown et al 1997, Nakata et al 1998.…”
Section: Discussionmentioning
confidence: 99%